Structural econometric modeling in industrial organization and quantitative marketing theory and applications - Hortaçsu, Ali; Joo, Joonhwi 1986- (Princeton University Press, 2023)
"A concise and rigorous introduction to widely used approaches in structural econometric modeling Structural econometric modeling specifies the structure of an economic model and estimates the model's parameters from real-world data. Structural econometric modeling enables better economic theory-based predictions and policy counterfactuals. This book offers a primer on recent developments in these modeling techniques, which are used widely in empirical industrial organization, quantitative marketing, and related fields. It covers such topics as discrete choice modeling, demand modes, estimation of the firm entry models with strategic interactions, consumer search, and theory/empirics of auctions. The book makes highly technical material accessible to graduate students, describing key insights succinctly but without sacrificing rigor. Concise overview of the most widely used structural econometric models Rigorous and systematic treatment of the topics, emphasizing key insights Coverage of demand estimation, estimation of static and dynamic game theoretic models, consumer search, and auctions Focus on econometric models while providing concise reviews of relevant theoretical models"--